PENGEMBANGAN MEDIA KARTU DOMINO MATERI PECAHAN UNTUK BELAJAR MANDIRI SISWA KELAS IV SDN 147 PEKANBARU DI MASA NEW NORMAL - Putri, Fardillah Zarani; Putra, Zetra Hainul; Munjiatun, Munjiatun (Jurnal Ilmiah Aquinas, 2021)
This study aims to develop domino card media of fraction for independent learning of fourth grade elementary school students in the new normal era. This research was motivated by the lack of learning media that can be used for students, especially when studying independently at home. The development of fraction domino card media was carried out using the method Research and Development (R&D) with the ADDIE (Analysis, Design, Develop, Implement, Evaluate) development procedure. The trial subjects of this study consisted of one-on-one trials with 3 student and limited trials with 4 students. This research was conducted in one of the homes of the fourth grade students of SDN 147 Pekanbaru in October 2020. The assessment of the validation of fraction domino card media products got a validation percentage score, namely media experts at 95.83% in the "Very Valid" category, and from material experts 89.06% with the "Very Valid" category. The overall student response to the fraction domino card media that was developed was 90.625% in the "Very Good" category and the response of the parents to the fractioned domino card media developed overall got a percentage score of 95.13% in the "Very Good" category. The implication of this research is that fraction domino card media has the potential to support students learning from home